BORROWING WORD IN SPORT RUBRIC OF ”JAWA POS” - MAKFUL, MEGA RIDZKIANTO (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Borrowing word, Part of speech, Sport rubric Jawa Pos. Language is known as human's culture product. It is created by human’s interactions. By the interactions, people start to make a connection one to others in order to make something which is called as communication. There are many ways in communication. The writer conducts a study about borrowing word in “Jawa Pos Newspaper Sport Rubric”which presents some borrowng words. There are two problems to be solved, they are: (1)What part of speech borrowed in the sport rubric on Jawa Pos newspaper (2)What types of English borrowing words in the sport rubric on Jawa Pos newspaper. This study uses descriptive qualitative approach to gather and analyze the data. It isincluded into document analysis because the researcher interprets the wordson sport rubric of Jawa Pos newspaper to answer the research problem.The result of the study,there areone hundred fourty one (141) English borrowing words foundin sport rubric Jawa Pos newspaper. The result of part of speech found in English borrowing word sport rubric on Jawa Pos newspaper (one hundred sixteen) nouns, (four) verbs, (twenty one) adjectives. The researcher finds types of borrowing word (ninety six) simple words, (thirty) complex words, and (fifteen) translated words.This study is conducted to identify English borrowing word. Therefore, the writersuggests the readers especially those who want to conduct the similar study to analyze deeply about all English borrowing words. The writer also suggests the next researchers to use other objects from different newspapers or different rubric of newspaper. The writer hopes that this study will be very helpful for the readers and the next researchers.